27.5k views
5 votes
-15-2g+6g=1+6g please help me solve this problem please

2 Answers

7 votes

Answer:

Explanation:

Isolate the variable by dividing each side by factors that don't contain the variable.

g

=

8

User Beko
by
4.6k points
5 votes

Answer:

g = -8

Explanation:

Both the left and the right sides of this equation -15-2g+6g=1+6g include the term 6g. Cancel these 6g terms. This leaves us with:

-15 - 2g = 1

Next, add 15 to both sides, to isolate the -2g term: -2g = 16

Solving for g via division by -2, we get: g = -8

User Hari M
by
4.3k points